Novyj metodologiceskij podchod v podgotovke specialistov-trenerov na vypuskajuscich kafedrach RGUFKa - Dement'ev, V. L. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The necessity of the transforming of the higher sports education for the new university level puts forward the number of concrete requirements to faculties of higher school for the perfection of specialists' training.